Italian cradle of chance calculus - Ostasiewicz, Walenty (Silesian Statistical Reviev, 2012)
Traditionally, the history of probability theory is dated for the year 1654, when a gambler de Méré proposed to Pascal two problems to solve. The problems were solved independently by B. Pascal and P. Fermat. One rather ignores that similar problems had been discussed and solved two hundred years earlier by Italian mathematicians. The article presents a sketch of the history of pre-Pascalian period of development of the doctrine of chances
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2012, Nr 10 (16), s. 121-129
Keywords: history of probability theory; problem of points; problem of dice; historia rachunku prawdopodobieństwa; problem podziału; problem kości do gry